Agrega valor el modelo Black-Litterman en portafo- lios del Mercado Integrado Latinoamericano (MILA)? Evaluación empírica 2008-2016 (2018)
The Black-Litterman model (BL) has been offered as an alternative to the classical Markowitz Mean-Variance framework, to structure well-diversified portfolios that incorporate visions from fundamental analysts. We apply this model to stock portfolios in the countries of the Mercado Integrado Latinoamericano (MILA): Colombia, Chile, Mexico and Peru, starting from the constituents of the main stock market indexes. As perspectives, we use the historical analyst ́s recommendations in Bloomberg for the period 2008-2016. We find that portfolios created with BL outperform the main index, both in average return and in alpha, in each of the four countries. Moreover, a regional BL portfolio that combines the four BL country portfolios, outperforms a regional Benchmark, measured in dollars, in each one of three alternatives of Us dollar hedge.